1988
DOI: 10.1021/np50060a006
|View full text |Cite
|
Sign up to set email alerts
|

Plant Antimutagenic Agents, 2. Flavonoids

Abstract: A number of known prenylated flavonoids were isolated from Psoralea corylifolia using an assay procedure based on inhibition of the mutagenic action of 2-aminoanthracene on Salmonella typhimurium (T-98). All of these compounds were toxic rather than antimutagenic or desmutagenic. Bakuchiol [17], a known prenylated phenolic terpene, was also isolated; its activity was not due to toxicity. Biochanin A [4], a known isoflavone, was similarly isolated from Cicer arientinum and was active and nontoxic. Some of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 9 publications
1
58
1
Order By: Relevance
“…Therefore, nobiletin exhibited more potency compared with kojic acid, by approximately two-fold. Nobiletin is a polymethoxyflavonoid occurring exclusively in Citrus fruits, 10) and has been reported to induce the differentiation of mice myeloid leukemia cells, 12) to exhibit antiproliferative activity toward a human squamous cell carcinoma cell line, 13) to exert anti-mutagenic activity, 14) and to suppress the induction of matrix metalloproteinase-9 and prostaglandin E 2 release. 15) In addition, nobiletin inhibits the combined endotoxin and cytokine-induced expression of nitric oxide synthesis and cyclooxygenase-2 proteins, and suppresses the formation of tumor promoter-induced edema 16) and papilloma 17) in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, nobiletin exhibited more potency compared with kojic acid, by approximately two-fold. Nobiletin is a polymethoxyflavonoid occurring exclusively in Citrus fruits, 10) and has been reported to induce the differentiation of mice myeloid leukemia cells, 12) to exhibit antiproliferative activity toward a human squamous cell carcinoma cell line, 13) to exert anti-mutagenic activity, 14) and to suppress the induction of matrix metalloproteinase-9 and prostaglandin E 2 release. 15) In addition, nobiletin inhibits the combined endotoxin and cytokine-induced expression of nitric oxide synthesis and cyclooxygenase-2 proteins, and suppresses the formation of tumor promoter-induced edema 16) and papilloma 17) in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has conˆrmed that plant ‰avo-noids inhibit the mutagenicity induced by chemical mutagens. [36][37][38][39][40][41] Nakasugi et al 42) reported that apigenin, hispidulin, genkwanin, and cirsimaritin in carqueja showed strong antimutagenic activities against Trp-P-2. Samejima et al 43) reported that luteolin, which is contained in peppermint, sage, and thyme, showed a strong antimutagenic eŠect against Trp-P-2.…”
Section: Discussionmentioning
confidence: 99%
“…is increasingly becoming a strong contender for cancer management. Coumarins, flavonoids, sesquiterpene lactones and edotides may be the principles in VA that are responsible for its anticancer activity [44][45][46].…”
Section: Vernonia Amygdalina (Va)mentioning
confidence: 99%